Serotonin Transporter Binding in the Human Brain After Pharmacological Challenge Measured Using PET and PET/MR - Silberbauer, Leo R.; Gryglewski, Gregor; Berroterán-Infante, Neydher; Rischka, Lucas; Vanicek, Thomas; Pichler, Verena; Hienert, Marius; Kautzky, Alexander; Philippe, Cecile; Godbersen, Godber M.; Vraka, Chrysoula; James, Gregory M.; et al. (Frontiers in Molecular Neuroscience, 2019)
Introduction: In-vivo quantification of the serotonin transporter (SERT) guided our understanding of many neuropsychiatric disorders. A recently introduced bolus plus constant infusion protocol has been shown to allow the reliable determination of SERT binding with reduced scan time. In this work, the outcomes of two methods, a bolus injection paradigm on a GE PET camera and a bolus plus infusion paradigm on a combined Siemens PET/MR camera were compared. Methods: 7 healthy subjects underwent paired PET and paired PET/MR scans each with intravenous double-blind application of 7.5 mg citalopram or saline in a randomized cross-over study design. While PET scans were performed according to standard protocols and nondisplaceable binding potentials (BPND) were calculated using the multi-linear reference tissue model, during PET/MR measurements [11C]DASB was applied as bolus plus constant infusion and BPND was calculated using the steady state method and data acquired at tracer equilibrium. Occupancies were calculated as the relative decrease in BPND between saline and citalopram scans. Results: During placebo scans, a mean difference in BPND of -0.08 (-11.71%) across all ROIs was found between methods. PET/MR scans resulted in higher BPND estimates than PET scans in all ROIs except the midbrain. A mean difference of -0.19 (-109.40%) across all ROIs between methods was observed for citalopram scans. PET/MR scans resulted in higher BPND estimates than PET scans in all ROIs. For occupancy, a mean difference of 23.12% (21.91%) was observed across all ROIs. PET/MR scans resulted in lower occupancy compared to PET scans in all ROIs except the temporal cortex. While for placebo, BPND of high-binding regions (thalamus and striatum) exhibited moderate reliability (ICC=0.66), during citalopram scans ICC decreased (0.36-0.46). However, reliability for occupancy remained high (0.57-0.82). Conclusion: Here, we demonstrated the feasibility of reliable and non-invasive SERT quantification using a [11C]DASB bolus plus constant infusion protocol at a hybrid PET/MR scanner, which might facilitate future pharmacological imaging studies. Highest agreement with established methods for quantification of occupancy and SERT binding potentials at baseline was observed in subcortical high-binding regions.